Multi-functional solvent-free SiO2 nanofluid simultaneously improve major properties and fluidity of epoxy resin: A new strategy beyond nanofillers. (April 2023) - Yuan, Jun; Zhu, Zongmin; Wang, Yadong; Yin, Xianze; Lin, Xuebao
Highlights: SiO2 NPES-P nanofluid (SiO2 NF) could act as accelerator for DDM cross-linking epoxy. A well mono-dispersion of SiO2 nanoparticles in epoxy matrix was obtained. SiO2 nanofluid improved fluidity and tg of EP resin simultaneously. Heat release and smoke production of EP/SiO2 NF composites were largely restrained. SiO2 NF enhanced the mechanical performance of EP due to good interfacial interaction. Abstract: High flowability and good wettability are the key advantages of liquid thermoset resin applied in high performance fiber reinforced composites. However, the adverse effects of powder flame retardants on processing stability of epoxy resin limits its application in vacuum assisted resin transfer molding (VARTM) process. A novel solvent-free SiO2 nanofluid (SiO2 NPES-P) was synthesized by ion exchange method, and the simultaneously improved flowability and higher glass transition temperature (Tg ) of EP/SiO2 NPES-P composites was obtained. The results showed that the nanofluid played a role as an accelerator of EP polymerization, which not only leaded to the decrease of curing temperature, but also improved the monodispersion of SiO2 nanoparticles and the compatibility between EP and nanofiller. This successful design results in EP composites with better thermal stability, Tg and mechanical properties than pure EP, which was hardly obtained by adding traditional nanofiller or liquid flame retardants. Moreover, EP/SiO2 NPES-P composites possessed better flame retardancy and smoke and heat suppression effects. With 5 wt% SiO2 NPES-P addition, LOI was increased to 28.5% from 22.0%, the peak heat release rate and total smoke product were reduced by 33.8% and 52.4%. The transparency of the EP was well preserved, indicating the successful avoidance of nanoparticle agglomeration. This work provides a new idea for low carbon manufacturing of flame-retardant EP composites. Graphical abstract: Image, graphical abstract